Low temperature synthesis of nano Ti(C, N) by novel mechanical and thermal activation method. (August 2015) - Xiang, D. P.; Lü, X. Y.; Ding, L.; Yang, Y. Z.; Liu, Y.; Tu, M. J.
Abstract : This paper presents a novel mechanical and thermal activation assisted carbothermal reduction (CR) method for synthesising Ti(C, N) powder at lower temperatures. Nano Ti(C, N) powder with approximately 30 nm grain size was synthesised by mixing powders of titanium, anatase, and carbon black. The starting powders were first milled for 10 to 40 h under N2 /Ar atmosphere, and then vacuum heat treated for 1 h at 800 to 1050°C. Consequently, nano Ti(C, N) powder with approximately 30 nm grain size was synthesised. X-ray diffraction analysis shows that Ti(C, N) is partially formed during mechanical milling, and the remaining reactants react completely below 1050°C. However, when the unmilled starting powders are heat treated at 1050°C under N2 for 1 h, large amounts of reactants remain. Thermogravimetry and differential scanning calorimetry analysis shows that the CR reaction of activated TiO2 occurs at a lower temperature under N2 than under Ar or vacuum.